Pengaruh Podcast Sebagai Media Pembelajaran Terhadap Hasil Belajar Siswa - Shanti Kurniasari; Desy Safitri; Sujarwo Sujarwo (Lembaga Pengembangan Kinerja Dosen, 2024)
In the learning process, using media for learning as a supporting tool is expected to adapt to increasingly sophisticated technological and informational developments. This review aims to examine the beneficial effects of using podcasts as educational tools in terms of the results of student learning in the current digital era. The review is structured based on a literature review or literature study. The method used in this research study is to identify and assess based on previously conducted and published research projects. Information obtained originates from books, journals, and articles with an expansive subject matter. The results of this research show the use of podcasts as a learning media can be helpful and progressively enhance students' learning results.